Market-Based Structural Top-Down Stress Tests of the Banking System - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2013)
Despite increased need for top-down stress tests of financial institutions, performing them is challenging owing to the absence of granular information on banks' trading and loan portfolios. To deal with these data shortcomings, this paper presents a market-based structural top-down stress testing methodology that relies in market-based measures of a bank's probability of default and structural models of default risk to infer the capital losses they could experience in stress scenarios. As an illustration, the methodology is applied to a set of banks in an advanced emerging market economy.